The development implications for social networks in working with domestic violence in rural Thailand through embedded mixed methods research - Tooltham, Pattanaphanu; Nakham, Mana (Kasetsart Journal of Social Sciences, 2026)
Domestic violence is a pervasive issue that plagues societies worldwide. It affects all members of society, including children, youth, women, men, and the elderly. Social networks play an integral role in addressing this challenge from the local to the global level. This study aims to develop guidelines for improving social networks’ efficacy in responding to domestic violence using embedded mixed-methods research. Qualitative research was used as the primary approach with interviews and focus group discussions conducted in two rural communities located in Udon Thani and Nong Khai Province in northeastern Thailand. Additionally, quantitative methods were employed through questionnaires distributed among 449 samples (n = 449) selected from four provinces representing social network representatives such as village chiefs, village health volunteers, social developers, local nurses, local police, and teachers among others. The analysis involved thematic analysis along with descriptive and inferential statistics to synthesize development implications for elevating mechanisms aimed at coping effectively with family abuse issues. The research identified eight key pathways that could be instrumental in enhancing social networks’ ability to address domestic abuse: adjusting people’s attitudes; creating awareness through projects or activities; developing databases based on stakeholder participation; expanding ideas into other areas; addressing complexities related to legal aspects of violence including mental health and drug abuse; rehearsing emergency plans with relevant staff; providing support tools and rewards for actors while designing models suitable for situational events unique to different regions. These points are crucial towards reducing cases of domestic violence during uncertain times.